Fibrin cross-linking in congenital factor XIII deficiency. Issue 5 (May 1980) - Rodeghiero, F; Barbui, T
Abstract : Homozygous patients with factor XIII deficiency are devoid of immunologically identifiable A protein, the active enzymatic component. Quantitative studies of transamidase activity of the factor are available in only a few cases, and the fibrin cross-linking pattern is not well known. The present paper deals with the quantitative estimation of factor XIII transamidase activity (dansylcadaverine system), factor XIII molecular subunits, and the corresponding fibrin cross-linking pattern in seven homozygous patients with factor XIII deficiency. The results indicate that transamidase activity was present in all patients, and the range was 0.5-1.7%. The pattern of fibrin stabiisation showed an absence of cross-linking in two patients, the presence of gamma-gamma-dimers (traces) in four, and gamma-gamma-dimers plus incomplete alpha-polymers (traces) in one patient. In conclusion, the homozygous patients reported here were not completely devoid of functioning factor XIII.